Evaluation of Incident Management in University using IT Infrastructure Library Framework - Batmetan, Johan Reimon; Mamonto, Julita Veronica; Muyu, Ronaldo (International Journal of Information Technology and Education, 2022)
Supporting the implementation of optimal services is a major need for organizations today. Guaranteed service management and good security is one of the benchmarks. This study aims to measure the level of incident management security at the Manado State University Computer Center. Incident Management is an intrinsic IT process that is visible to both customers and businesses. An organization proactively implements a sound IT service management framework such as ITIL v3 so as to maintain the desired Quality of Service (QoS). Data analysis uses Likert scale calculations and refers to aspects of maturity.